Application of the antimicrobial peptide ctx(ile21)-ha in peanut seeds to evaluate their germinative parameters - Brandão, Lorenza Eivazian Vianna Nogueira [UNESP]; Onório, Valentina Lou de Andrade [UNESP]; Melo, Luana Fernandes [UNESP]; Leite, Wendell Queiroz [UNESP]; Vicente, Eduardo Festozo [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2024)
Antimicrobial peptides have gained prominence in scientific research due to their biological potential and antifungal capacity. These peptides are small proteins intrinsic to the system of many living organisms and have activity against microorganisms, bacteria, fungi, viruses and helminths. Therefore, fungi of the genus Aspergillus spp are very common in nature, and affect the production of peanuts, almonds, chestnuts and others. Thus, the present work sought a strategy to reduce or mitigate the activity of this fungus in peanut seeds during germination by applying three different dosages (3.6, 4.8 and 7.2 mg/mL) of the antimicrobial peptide Ctx(Ile21)-Ha in ultrapure water, and had as objective to evaluate its effects on germination parameters in comparison with the use of the commercial fungicide (Mayran), widely used in peanut crops in the Tupã-São Paulo. The most promising results occurred with dosages of 3.6 mg/mL and 7.2 mg/mL of the peptide, and the Mayran fungicide also showed high efficiency rates for peanut germination, but it presents high toxicity for the producer who handles the fungicide.
Keywords: Fungicide; Germination; Microorganisms; Peptide; Production